2016
DOI: 10.1111/jace.14137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yb Codoping on the Phase Transition, and Electrical and Photoluminescence Properties in KNLN:Er/xYb Ceramics

Abstract: Ceramics 0.94(K 0.5 Na 0.5 )NbO 3 -0.06LiNbO 3 :Er/xYb with x = 0, 0.002, 0.004, 0.006, 0.008 were fabricated in this study, and phase structure, dielectric, piezoelectric, ferroelectric, and upconversion photoluminescence properties of the ceramics were systematically studied. Results show that all ceramics are in the polymorphic phase transition region near room temperature. However, a relaxor-like phase transition was observed as Yb increasing to over x = 0.004. The optimized dielectric, piezoelectric, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The insets of Figure display the schematic structures of these compositions from the orthorhombic phase to PPT, and finally transformed into tetragonal phase. Note that, the absence of secondary impurity phase assigned to K 5.75 Nb 10.85 O 30 (PDF#38‐0297), which is commonly presented in KNN‐based ceramics in these synthesized samples, is a remarkable advance in this study. Such advancement could be ascribed to the efficiently supplement of K + and Na + evaporation during sintering.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The insets of Figure display the schematic structures of these compositions from the orthorhombic phase to PPT, and finally transformed into tetragonal phase. Note that, the absence of secondary impurity phase assigned to K 5.75 Nb 10.85 O 30 (PDF#38‐0297), which is commonly presented in KNN‐based ceramics in these synthesized samples, is a remarkable advance in this study. Such advancement could be ascribed to the efficiently supplement of K + and Na + evaporation during sintering.…”
Section: Resultsmentioning
confidence: 66%
“…The X‐ray powder diffraction patterns of KNN– x LN:0.006Eu 3+ ceramics are displayed in Figure . The phase structure can be determined by the relative height between the two split peaks around 45.5° . When x ≤ 0.05, the (202) peak is higher than the (020) peak, indicating that KNN– x LN:0.006Eu 3+ ceramics have a major orthorhombic phase (O phase) at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jia et al reported dual‐enhancement between the ferro‐/piezoelectric polarization and the photoluminescent performance of rare earth Pr 3+ ‐doped (K 0.5 Na 0.5 )NbO 3 (KNN) lead‐free ceramics, and observed the polarization‐induced luminescent enhancement . Similar behavior is also observed in Er/Yb co‐doped 0.94(K 0.5 Na 0.5 )NbO 3 –0.06LiNbO 3 or Pr 3+ ‐modified 0.93(Bi 0.5 Na 0.5 )TiO 3 –0.07BaTiO 3 ceramics . Up to now, Ln‐doped KNN‐based materials have drawn many researchersʼattentions, the focus of attention is to realize the coexistence of ferro‐/piezoelectric and luminescent properties, and investigate the relationship between them.…”
Section: Introductionmentioning
confidence: 69%
“…The studies on KNN materials mainly focus on the enhancement of its piezoelectric properties. Nowadays, many groups take advantage of the ferro‐/piezoelectric properties of KNN host in combination with lanthanide ions acting as activators, realizing the simultaneous existence of ferroelectric and optical properties . These interesting characteristics also provide an opportunity for us to develop a series of “smart” materials with luminescent emission, which can be modulated by external stimuli of electric field, magnetic field, mechanical force, or temperature (Scheme ).…”
Section: Introductionmentioning
confidence: 99%